Impact of insulin reduction on glycemic control in children attending a residential diabetes camp. Issue 8 (3rd September 2019) - Lo, Huay‐Lin; Adhikari, Soumya; White, Perrin C.; Grishman, Ellen K.; Gupta, Olga T.
Abstract: Background/Objectives: Children attending diabetes camp are more active, increasing the risk of hypoglycemia. Decreasing initial insulin doses may reduce this risk. The objectives of our study were to compare glycemic control between campers receiving multiple daily injections (MDI) and continuous subcutaneous insulin infusion (CSII), and analyze the impact of decreasing basal insulin by 10%. Methods: We analyzed 849 camp sessions (599 children, 5‐19 years old) from Camp Sweeney's 2016/2017 summers. Campers were separated into groups by year and insulin route (MDI_2016, MDI_2017, CSII_2016, and CSII_2017). The MDI_2016 group had initial basal insulin decreased 10%, while CSII_2016, MDI_2017, and CSII_2017 did not. Time spent in blood glucose ranges and area under the curve (AUC) were compared by year and insulin route using ANOVA. We also performed repeated measures ANOVA using campers who attended both years. Results: No significant differences in time spent in any glucose range could be attributed to the initial 10% basal decrease, including on paired analysis. MDI_2017 had more decreases to basal insulin than the other groups. CSII campers had higher AUC and more hyperglycemia than MDI campers. Conclusions: Campers on MDI may benefit from decreasing basal insulin, either at the beginning of camp or during the first week. Future research is needed to optimize glycemic control in the camp setting.